The Effects of Some Climate Factors upon Frequency Distribution of Local Sandflies Breed in Misan Province, Iraq - Alsaad, Rasha K A; Kawan, May H (The Iraqi Journal of Veterinary Medicine, 2021)
The genus Phlebotomus is naturally responsible for the transmission of many protozoal parasites like Leishmania. The study was conducted to determine the effect of some climate factors on sandflies distribution over a year from December 2019 to November 2020. A total of 268 sandflies of both sexes were collected from different areas in Misan province, Iraq. Sandflies were collected using light traps and stick oil paper, then placed in cups or Petri dishes containing sterile normal saline for examination. The current study showed an inverse relationship between the presence and number of sandflies with temperatures. Rainfall had a significant impact on parasite distribution, while wind speed had a potential impact on sandfly activity. The percentage of female sandflies was significantly (P<0.05) higher than that of males (54.85% for females versus 45.15% for males). In conclusion, heavy precipitation is the main climate factor that affects the frequency distribution of local breed sandflies followed by rising temperature degrees that are seen in the summer season. The climate can affect the activity, spreading, and distribution of sandflies with detected one peak of their activity in December.